2013
DOI: 10.1021/jp408627e
|View full text |Cite
|
Sign up to set email alerts
|

Novel Heterojunction Bi2O3/SrFe12O19 Magnetic Photocatalyst with Highly Enhanced Photocatalytic Activity

Abstract: Magnetic composite photocatalyst Bi2O3/SrFe12O19 was synthesized by hydrolysis with medium temperature sintering method. X-ray diffraction (XRD) investigation revealed that introduction of SrFe12O19 did not change the favorite growth direction of Bi2O3, [121] orientation. Micromorphology study indicated that SrFe12O19 was distributed on the surface of Bi2O3 to possess the best possibility of forming some heterojunction structures. Vibrating sample magnetometer (VSM) measurements manifested the composite posses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(50 citation statements)
references
References 31 publications
3
45
0
Order By: Relevance
“…This spectrum of BiVO 4 /Mn 1−x Zn x Fe 2 O 4 (15 wt %) could confirm the coexistence of Mn 1−x Zn x Fe 2 O 4 and BiVO 4 in the prepared composite, which indicated that BiVO 4 /Mn 1−x Zn x Fe 2 O 4 (15 wt %) was prepared successfully. In addition, the absorption patterns at 2341.7 cm −1 and 3433.6 cm −1 were attributed to CO 2 and the surface adsorption H 2 O [9]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This spectrum of BiVO 4 /Mn 1−x Zn x Fe 2 O 4 (15 wt %) could confirm the coexistence of Mn 1−x Zn x Fe 2 O 4 and BiVO 4 in the prepared composite, which indicated that BiVO 4 /Mn 1−x Zn x Fe 2 O 4 (15 wt %) was prepared successfully. In addition, the absorption patterns at 2341.7 cm −1 and 3433.6 cm −1 were attributed to CO 2 and the surface adsorption H 2 O [9]. …”
Section: Resultsmentioning
confidence: 99%
“…This prevents it application as a wastewater treatment. Fortunately, a magnetic photocatalyst could solve the above issue [8,9]. The exploitation and application of various magnetic photocatalyst materials have been boosting scientists’ morale.…”
Section: Introductionmentioning
confidence: 99%
“…7) results confirm that we succeeded in synthesizing core/ shell style (SFO/Fe 3 O 4 ) nano-composite magnets. There have been other successful synthesis approaches to synthesize Sr or Ba hexaferrite/soft magnet composites, [27][28][29] although previous work targeted different applications rather than permanent magnets. Multi-step methods like the one presented here are well suited for synthesizing core/shell structures 14 that allow more control on the morphology and amount of individual phase (hard and soft) needed for producing coupled permanent magnets.…”
mentioning
confidence: 99%
“…The strong peaks at low frequency (about 520 cm À1 and 715 cm À1 ) in both spectra of BiOBr and 75% BiOBr/Bi 2 O 3 are attributed to the BieO vibration of chemical bonds in BiOBr. In the FT-IR spectra of 75% BiOBr/Bi 2 O 3 , the characteristic peak of Bi 2 O 3 at 432.8 cm À1 [28] and the characteristic peak of BiOBr at 520 cm À1 and 715 cm À1 both appear [29], which prove the existence of Bi 2 O 3 and BiOBr in 75% BiOBr/Bi 2 O 3 composites.…”
Section: Crystal Structure and Morphologymentioning
confidence: 75%